The Effectiveness of Short-Term Psychodynamic Psychotherapy on Improving Object Relations Problems and Borderline Personality Disorder Symptoms: The Mediating Role of Mentalization Capacity - Sharifian, Moein; Haddadi, Katauon; Zeinolabedini , Mitra; Norouzi , Arezoo (Mental Health and Lifestyle Journal, 2026)
The objective of this study was to examine the effectiveness of short-term psychodynamic psychotherapy on object relations problems and borderline personality disorder symptoms and to investigate the mediating role of mentalization capacity in this therapeutic process. This quasi-experimental study employed a pretest–posttest design with follow-up and included an experimental group receiving short-term psychodynamic psychotherapy and a control group placed on a waiting list. Sixty adults diagnosed with borderline personality disorder were recruited from outpatient clinics in Tehran and randomly assigned to the two groups. The experimental group received twelve weekly individual psychotherapy sessions, while the control group received no intervention during the study period. Assessments were conducted at baseline, post-intervention, and six-week follow-up using standardized measures of borderline symptom severity, object relations functioning, and mentalization capacity. Data were analyzed using mixed-design analysis of variance and regression-based mediation analysis with bootstrapping. Mixed-design ANOVA revealed significant Time × Group interaction effects for borderline personality disorder symptoms (F = 48.62, p < .001, η² = .46), object relations problems (F = 52.19, p < .001, η² = .49), and mentalization capacity (F = 45.73, p < .001, η² = .44), indicating substantial improvements in the experimental group that were maintained at follow-up. Mediation analysis demonstrated that increases in mentalization capacity significantly mediated the effects of psychotherapy on reductions in borderline symptoms and object relations difficulties, with significant indirect effects based on bootstrapped confidence intervals. Short-term psychodynamic psychotherapy produces robust and sustained improvements in borderline symptomatology and object relations functioning, and these therapeutic effects are partially explained by enhancements in mentalization capacity, highlighting mentalization as a core mechanism of change.